Análise Filogenética de Cratomorphini Green, 1959 (Coleoptera: Lampyridae, Lampyrinae) - LIMA, WILLIAM (Entomologia, 2023)
The New World firefly fauna includes several giant (>25mm) firefly species in the Lampyrine tribes Cratomorphini and Lamprocerini. Their overlapping genus-level diagnoses are based on a few traits related to sexual signaling known to be fast-evolving and labile within-genus in Lampyrine. To clarify the taxonomy and investigate morphological evolution in Cratomorphini and closely related taxa, we inferred the phylogenetic relationships of 49 terminals representing 35 species, including five of seven Cratomorphini genera. Our phylogenetic analyses included 96 adult morphological characters and contrasted the results of Maximum Parsimony Analysis and Bayesian Inference. Consistent with recent analyses based on genomic data, Cratomorphini was recovered as polyphyletic, with four distinct clades, as follows: (i) Cratomorphus (partim: the type species, C. splendidus and associated species) + Erythrolychnia; (ii) Cratomorphus (partim; transferred here to Nyctocera gen. nov.); (iii) Cratomorphus (partim; transferred here to Bituca gen. nov.) and (iv) Micronaspis + (Aspisomoides + Pyractomena) + Aspisoma. Cratomorphus was found polyphyletic, with three lineages: the typical Cratomorphus i.e. associated with C. splendidus); a branch within the Lamprocerini, and a third branch in a deeper polytomy within Lampyrinae. As such, we redefine and establish new diagnoses for Cratomorphini, and propose a new tribe (Aspisomaini trib. nov.) and two new genera (one in Lamprocerini sensu nov. and another one in incertae sedis). We transferred four species from Cratomorphus sensu nov. – three to the Lamprocerini sensu nov., Nyctocera gen. nov., and one to the incertae sedis Bituca gen. nov.,– all of which redescribed after the study of type specimens. We provide illustrations of diagnostic features of all new taxa; keys to Cratomorphini sensu nov., Aspisomaini trib. nov., Lamprocerini sensu nov., genera, and to species of the new taxa.
Systematics of giant neotropical fireflies and their kin: (Lampyridae: Lampyrinae)